2017
DOI: 10.1111/trf.14267
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem‐induced immune thrombocytopenia and the diagnostic process of laboratory testing

Abstract: Drug-induced immune thrombocytopenia should be considered in cases of acute thrombocytopenia in patients undergoing meropenem treatment. Clinicians should be cognizant of DITP, and a definitive diagnosis should be pursued, if feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…The absence of drug-dependent antibody testing and bone marrow aspiration prevent us from drawing a firm conclusion regarding the mechanism of meropeneminduced pancytopenia in the present case. However, the hematological findings with the progressive development of thrombocytopenia, anemia, and then neutropenia suggest a possible mechanism of suppression of granulopoiesis or antibody-mediated destruction, as reported in recent studies [5,6].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The absence of drug-dependent antibody testing and bone marrow aspiration prevent us from drawing a firm conclusion regarding the mechanism of meropeneminduced pancytopenia in the present case. However, the hematological findings with the progressive development of thrombocytopenia, anemia, and then neutropenia suggest a possible mechanism of suppression of granulopoiesis or antibody-mediated destruction, as reported in recent studies [5,6].…”
Section: Discussionsupporting
confidence: 55%
“…A case report by Estella and colleagues [21] described meropenem-induced pancytopenia in a 3-year-old patient at 100 mg/kg given every 8 hours to manage the regrowth of meropenem-sensitive Morganella morganii in CSF cultures. Huang et al [6] reported a case of meropenem-induced immune thrombocytopenia in a 59-year-old patient, by detecting meropenem-dependent platelet antibodies and platelet count recovery after discontinuation of meropenem. Oka et al [5] reported the development of severe anemia with clinical signs in a 76-year-old female patient, who received 2 g meropenem per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanai et al [12] found that 48.4% of patients on linezolid developed thrombocytopenia [12]. Meropenem has also been linked with the platelet abnormality [13]. In this survey, 86.2% of patients receiving antibiotics developed thrombocytopenia (p = 0.001).…”
Section: Discussionmentioning
confidence: 59%
“…There was the report that Meropenem® induced the transient coagulation factor X deficiency of a 12-month-old boy suffering from 25% TBSA and underwent hypocoagulability 3 days after the initiation of the antibiotic. And it is also considered to be responsible for drug-induced immune thrombocytopenia (DITP) that shows acute thrombocytopenia in patients [17]. The mechanism of Meropenem® to initiate different ways of coagulopathy still needs further investigation; however, in present case treatment, long-term usage of Meropenem® might eradicate vitamin K producing intestinal microflora, interdicted the vitamin K2 pathway and made it deprived of vitamin K storage in the patient.…”
Section: Discussionmentioning
confidence: 99%